Debris Accumulation Patterns on Talus Slopes in Surprise Valley, Alberta - Luckman, Brian (Géographie physique et Quaternaire, 1988)
ABSTRACTThis paper presents the results of the measurement of debris accumulation processes, patterns and volumes at seven sites over a 13-year period in Surprise Valley, Alberta, Canada. Mean accumulation rates range up to ca 5 mm/yr and are strongly influenced by the amount and frequency of snow avalanche activity. All talus slopes studied experienced avalanches during the 13-year period and avalanche erosion is important in modifying and reworking the surface of these slopes. Mapped depositional patterns on selected slopes indicate deposition is more probable and usually greater on upper an middle slopes but avalanche erosion may result in greater volumes of deposition on lower slopes in some years (almost one year in two at the most active sites). There is high year-to-year and site-tosite variation in avalanche activity indicating that local, site specific controls are the most important determinant of depositional patterns. Rockfall amounts are underestimated by the point sampling techniques used in this study. Limited available data suggest rockfall inputs to the talus exceed those by snow avalanches (much of the avalanche deposition is reworked from upslope) and a least two major debris-flow generating events were recorded over a 13-year period.